PENGEMBANGAN E-MODUL FISIKA BERBASIS LITERASI SAINTIFIK PADA MATERI USAHA DAN ENERGI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Sunda, Arianti Andriyani; Harso, Aloisius; Kaleka, Melkyanus B. Umbu (PendIPA Journal of Science Education, 2025)
This study aimed to determine the feasibility, practicality, and effectiveness of a scientific literacy-based physics e-module on the topic of work and energy to improve students’ learning outcomes.This is a research and development (R&D) study employing the ADDIE development design. The research subjects consisted of a four validators, comprising two lecturers as media experts and two science/physics teachers as material experts, as well as two science/physics teachers and 32 students of SMP Negeri 2 Ende. Data were collected using questionnaires and pretest–posttest. The data were analyzed using the N-gain test.The results of the study show that the developed product is highly feasible for use as a learning resource, with a media expert assessment score of 88.75% and a material expert assessment score of 95.00%, both falling under the “highly feasible” category. The trial results from subject teachers and students indicate that the developed scientific literacy-based physics e-module is highly feasible for use, with an average score of 100% from subject teachers and 81.33% from students. Learning science/physics using the scientific literacy-based physics e-module can positively influence students’ learning outcomes, as evidenced by the N-gain test result of 0.81, which falls under the “high” category. The effectiveness test result reached 100%, categorized as “highly effective.” These findings indicate that the scientific literacy-based physics e-module is both highly feasible and highly effective for use.